Susceptibility to infectious diseases : the importance of host genetics - Bellamy, Richard (Richard John) (Advances in molecular and cellular microbiology, 2004)
Extensive evidence has now accumulated that host genes are important determinants of the outcome of infection for many common pathogens. This book, written by leading authorities, summarises the advances which have been made in understanding the complexity of host genetic susceptibility.